Air bubble entrapment during drop impact on solid and liquid surfaces. (April 2022) - Halder, Subhayan; Granda, Rafael; Wu, Jingwei; Sankaran, Abhilash; Yurkiv, Vitaliy; Yarin, Alexander L.; Mashayek, Farzad
Highlights: A coupled phase-field and the Navier-Stokes model describing drop impact onto a solid dielectric surface is developed. The phase-field model is based on the advective Cahn-Hilliard equation. The simulation results of the drop impact onto a solid parafilm surface compare well with the experimental observations. Critical regimes of air bubble formation using non-dimensional Weber and Froude numbers are identified. Abstract: The phase-field modeling (PFM) of water drop impact onto a dielectric hydrophobic parafilm surface is performed to explore air entrapment and its influence on deposition and rebound phenomena. Local and global characteristics of the drop impact are taken into account by using the combined Cahn-Hilliard and Navier-Stokes equations. The modeling results of water drop impact are directly compared with our experimental measurements in terms of maximum spreading distance, and air bubble size. The simulation results reveal that air can be trapped under the liquid drop during the initial impact as well as during the retraction phase at the center of the drop due to the closure of the liquid layer above a cavity. It is found that the drop diameter and the impact velocity play significant roles in the air entrapment phenomena. The probability of air bubble formation is higher at lower impact velocity and for larger drop size. The model is also capable of simulating the case of drop impact onto a water surface, and the results are validated using prior literature data. In addition, the influence of the phase-field variables and the mesh adaptation scheme on the PFM is studied and discussed. Thus, our findings provide new qualitative and quantitative insights into the influence of air entrapment on drop deposition onto hydrophobic and liquid surfaces.